Comprehensive characterization of ligand‐induced plasticity changes in a dimeric enzyme. (7th July 2016) - Baettig, Oliver M.; Shi, Kun; Yachnin, Brahm J.; Burk, David L.; Berghuis, Albert M.
Abstract : An enzyme's inherent structural plasticity is frequently associated with substrate binding, yet detailed structural characterization of flexible proteins remains challenging. This study employs complementary biophysical methods to characterize the partially unfolded structure of substrate‐free AAC(6′)‐Ii, an N ‐acetyltransferase of the GCN5‐related N ‐acetyltransferase (GNAT) superfamily implicated in conferring broad‐spectrum aminoglycoside resistance on Enterococcus faecium . The X‐ray crystal structure of AAC(6′)‐Ii is analyzed to identify relative motions of the structural elements that constitute the dimeric enzyme. Comparison with the previously elucidated crystal structure of AAC(6′)‐Ii with acetyl coenzyme A (AcCoA) reveals conformational changes that occur upon substrate binding. Our understanding of the enzyme's structural plasticity is further refined with small‐angle X‐ray scattering and circular dichroism analyses, which together reveal how flexible structural elements impact dimerization and substrate binding. These results clarify the extent of unfolding that AAC(6′)‐Ii undergoes in the absence of AcCoA and provide a structural connection to previously observed allosteric cooperativity of this enzyme. Database: Structural data are available in the PDB database under the accession number5E96 . Abstract : This study reports the first apo X‐ray crystal structure of the antibiotic resistance enzyme AAC(6′)‐Ii, and utilizes small‐angle X‐ray scattering and circular dichroism to characterize the inherent structural plasticity and ligand binding‐induced conformational changes. These structural analyses provide insight into allosteric cooperativity of ligand binding.